2020
DOI: 10.1101/2020.08.13.250035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Swimming direction of the glass catfish is responsive to magnetic stimulation

Abstract: Throughout evolution, organisms have developed unique strategies to become more competitive in their environment. One unique adaptation is the ability to sense magnetic fields, i.e., magnetoreception. While animals like salmonids, pigeons, eels and sea turtles use magnetoreception to migrate over thousands of kilometers [1-10], non-migratory fish species have also shown evidence of magnetoreception [11, 12]. The freshwater fish, Kryptopterus bicirrhis is known to be sensitive to the Earth's magnetic field [13-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Here we tested if the magnetic elds induced during a seizure in the established kainic acid (KA) rat model 27 could be used both as the sensor and the activator to suppress seizure activity in an animal model. We capitalized on a recently discovered membraneassociated protein that is sensitive to magnetic elds, the Electromagnetic Perceptive Gene (EPG) [28][29][30][31] ; it was demonstrated that remote activation of EPG by electromagnetic elds signi cantly increases intracellular calcium concentrations, indicative of cellular excitability 32 . Thus, we tested if EPG expressed in inhibitory hippocampal interneurons will be sensitive to the magnetic elds generated during a seizure, that in turn will activate the inhibitory interneurons which will shut down or disrupt the circuit, interrupting seizure activity and progression in a closed-loop and cell-speci c fashion.…”
Section: Page 3/17mentioning
confidence: 99%
“…Here we tested if the magnetic elds induced during a seizure in the established kainic acid (KA) rat model 27 could be used both as the sensor and the activator to suppress seizure activity in an animal model. We capitalized on a recently discovered membraneassociated protein that is sensitive to magnetic elds, the Electromagnetic Perceptive Gene (EPG) [28][29][30][31] ; it was demonstrated that remote activation of EPG by electromagnetic elds signi cantly increases intracellular calcium concentrations, indicative of cellular excitability 32 . Thus, we tested if EPG expressed in inhibitory hippocampal interneurons will be sensitive to the magnetic elds generated during a seizure, that in turn will activate the inhibitory interneurons which will shut down or disrupt the circuit, interrupting seizure activity and progression in a closed-loop and cell-speci c fashion.…”
Section: Page 3/17mentioning
confidence: 99%
“…For each application our goal was to design an electromagnet that can deliver the desired magnetic flux given various constraints including power consumption, coil and sample temperature, and coil size. Evidence suggests that applying magnetic flux densities >50 mT (Wheeler et al, 2016;Krishnan et al, 2018;Hunt et al, 2021) was successful at eliciting responses in magnetoreceptive targets. Thus, shows a set of three-coils which can be stacked and used for stimulating samples on a multiwell plate with a relatively uniform field.…”
Section: Applicationsmentioning
confidence: 99%
“…Development of magnetic sensitive pathways, like those using nanoparticles (Chen et al, 2015) and proteins like the electromagnetic perceptive gene (EPG) (Krishnan et al, 2018;Mitra et al, 2020;Cywiak et al, 2020;Hwang et al, 2020;Hunt et al, 2021) have contributed to making magnetic stimulus delivery for wide ranging applications increasingly important. Furthermore, recent studies which show that humans may also have magnetoperception (Wang et al, 2019) serve to increase the demand for easy to implement and versatile electromagnetic stimulation devices.…”
Section: Introductionmentioning
confidence: 99%
“…Here we tested if the magnetic fields induced during a seizure in the established kainic acid (KA) rat model 27 could be used both as the sensor and the activator to suppress seizure activity in an animal model. We capitalized on a recently discovered membrane-associated protein that is sensitive to magnetic fields, the Electromagnetic Perceptive Gene (EPG) [28][29][30][31] ; it was demonstrated that remote activation of EPG by electromagnetic fields significantly increases intracellular calcium concentrations, indicative of cellular excitability 32 . Thus, we tested if EPG expressed in inhibitory hippocampal interneurons will be sensitive to the magnetic fields generated during a seizure, that in turn will activate the inhibitory interneurons which will shut down or disrupt the circuit, interrupting seizure activity and progression in a closed-loop and cell-specific fashion.…”
Section: Introductionmentioning
confidence: 99%